UTILIZATION OF YOUTUBE SOCIAL MEDIA IN INCREASING AWARENESS OF HISTORY - Siti Roudotul Fadillah; Jumardi Jumardi (PEDAGOGIA, 2022)
The rapid development of information and communication technology (ICT) can make it easier for everyone to access various types of information through the internet and social media; this can result in a decline in national identity in society. Meanwhile, technological developments can also be used as a medium to educate the general public. Therefore, this study aims to obtain information on how to use YouTube social media to increase historical awareness. The research method uses qualitative research methods with a case study approach, while the data collection procedures include observations, interviews, and documentation. Informants in this study consisted of founders of historical creators on Youtube and several general audiences. The results of this study suggest that the use of social media in increasing historical awareness on the Inspect History Youtube account by utilizing animated videos is one of the efforts that can be made to provide historical knowledge and its relation to increasing historical awareness in the current digital era.